Simultaneous identification of species and molecular forms of the Anopheles gambiae complex by PCR-RFLP. - Fanello, C; Santolamazza, F; della Torre, A (2002)
For differential identification of sibling species in the Anopheles gambiae Giles complex (Diptera: Culicidae), including simultaneous separation of M and S molecular forms within An. gambiae Giles sensu stricto, we describe a PCR-RFLP method. This procedure is more efficient, faster and cheaper than those used before, so is recommended for large-scale processing of field-collected larval and adult specimens to be identified in malaria vector studies.